ANALISIS WACANA KRITIS TERHADAP FATWA BAHTSUL MASA’IL TENTANG PEREMPUAN - Musarrofa, Ita (ULUL ALBAB Jurnal Studi Islam, 2017)
This article examines the fatwa of Bahtsul Masa’il on women using Critical Discourse Analysis. Two matters of research problem is how Bahtsul Masa’il fatwa on women and how the Critical Discourse Analysis of the fatwa Bahtsul Masa’il about women. There are twelve fatwa on women decided by Bahtsul Masa’il forum, seven of which talk about the role of women in the public world. They were analyzed using Critical Discourse Analysis framework involving three levels of analysis, namely text, social cognition and context. Texts of Bahtsul Masa’il decision on women represent women as being vulnerable to libel and can bring slander. Women are also represented as weak creatures who need supervision and protection of men. Fatwa text that is bias arises from the procedure of making fatwa which highly favor the yellow book. While the yellow book itself tends to put women in the private sphere and look down on women. In addition, the frame of the community producing Bahtsul Masa’il fatwa (religious leader and religius students) are also the result of the internalization of norms and values of yellow book as the idol at the pesantren. In context level, the fatwa which tends to give a negative identity toward women is born out of the context of the patriarchal society.